Electricity supply reliability and households decision to connect to the grid - Arnaud Millien (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
The 7th Sustainable Development Goal aims to "ensure access to affordable, reliable, sustainable and modern energy for all". Because the cost to increase electrical capacity in Africa alonehas been estimated at 800bn, this article investigates the extent to which electricity reliability could contribute to a reduction in the marginal cost of grid extension by attracting more customers. Using lightning as an instrument for outages severity, the article evaluates the assumption that less uncertainty about electricity availability would lead to a larger number of connected households.The article finds that a one percentage point increase in electricity reliability would yield a 0.67 percentage point increase in connections. Therefore, delivering fully reliable electrical power would allow an electricity company to achieve its targeted growth of customer base 15 months earlier than planned.The effect of reliability is highest for middle-rich households, which are the most reluctant to subscribe in the presence of total, severe or partial outages. A one-percentage-point upgrade in reliability increase the likelihood that these households will be connected by 1.28 percentage points.This article also finds that households are more sensitive to outages in areas where outages are less frequent. In addition, the impact of reliability on households decision to connect could be at least 5% greater than the effect of poverty ; if the frequency of outages is too high, the wealth or poverty effect might vanish and households would respond only to the excessively low reliability.These results confirm the uncertainty assumption, that is, regular and severe outages yield an uninsurable context that deters households from subscribing to the electric service.
Keywords: Q4; Q1; O18; O55; C26; C52; 330; electrification; reliability; outages; Kenya; instrumental variable